Adsorption Studies of Synthetic Batik Dye (SBD) Using Granular Activated Carbon (GAC) : Batch Process - Normimi Fatihah, Ibrahim (2012)
Batik industry is a very famous textile industry in Malaysia especially in East Coast of Peninsular Malaysia. Started in small scale, today it has become one of the highest economic growths in Malaysia due to high demands locally and from abroad. However, the wastewater from textile industry contributes to water pollution since it utilizes a lot of chemicals. Preliminary studies show that the wastewater from this homemade textile industry contains grease, wax, heavy metal, surfactant, suspended solid, and dyes (organic and inorganic). This research was done to study the potential of granular activated carbon (GAC) for the adsorption of synthetic batik dye (SBD) from aqueous solution by the variation of solution with different contact time, adsorbent dosage and initial concentration of SBD. Activated carbon (AC) is commonly known as one of the great adsorbents in adsorption process. For this study, granular activated carbon (GAC) has been used since it is preferred for all adsorption of gases and vapors as their rate of diffusion are faster. The synthetic batik dye has been chose because the research about this topic has not been done yet. There are three parameters that will be investigated; effect of adsorbent dosage (w), effect of contact time and effect of initial synthetic batik dye concentration. All results from the experiment were being analyzed using UV-Visible Spectrophotometer (UV-Vis). The results show that the color of the dye changes with different contact time, adsorbent dosage and also different initial concentration of synthetic batik dye. The data collected could be used to improve the effectiveness of dye removal from the batik industry wastewater using granular activated carbon (GAC). The research showed the applicability of GAC to adsorb the color of SBD. For SBD initial concentration shows the highest percentage concentration difference which is 69.75 % occurring at 0.2 g/L. While for adsorbent dosage, the highest dosage which is 60 gram get the highest percentage; 94.77 %. And for contact time, the longest contact time which is 20 minutes gets the highest percentage where the percentage is 95.06 %.